YOUTH SCIENTIFIC AND PRACTICAL CONFERENCE«METHODOLOGY AND THEORY OF LOCAL POLICY RESEARCH»: REPORT ON THE LAST SCIENTIFIC EVENT - Vitkovskaya, T.B. (Perm Federal Research Centre Journal, 2015)
The article gives an overview of the scientific activities of the Division for research of political institutions and processes of the Perm Scientific Center of UB RAS - Youth conference on theoretical and methodological problems of studying local politics. The reason for the relevance of the selected aspect of the topic was described. The following topics were discussed at the conference: the problem field of research methodology of local case studies; methodology of the study of electoral processes on the local level; learning strategies of protest and activism in local communities; research methodology of local identity.